Co-Hydrothermal Carbonization: An Innovative Solution for Enhancing National Energy Resilience Through the Production of Clean Solid Fuels from Sewage Sludge and Coal Slime - Ardyanto, Fakhriyan; Sakina, Zafira Naja; Thamrin, Suyono; Laksmono, Rudy (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2026)
Waste management, particularly the handling of sewage sludge generated from water treatment and coal slime as a byproduct of mining activities, poses a serious environmental challenge. Co-Hydrothermal Carbonization (co-HTC) technology has emerged as an innovative solution to convert these two types of waste into clean and efficient solid fuel. This study aims to explore the characteristics of the co-HTC process, the environmental benefits it offers, the implementation challenges it faces, and its potential applications in supporting a sustainable energy transition. The research employs a literature review approach, gathering information from scholarly articles, research reports, and policy documents related to co-HTC. The selection of literature is based on topic relevance, publication year, and the quality of research methodology. A critical analysis identifies the main characteristics of co-HTC technology, its environmental benefits, implementation challenges, and application opportunities. The findings indicate that co-HTC can significantly reduce waste volume and produce hydrochar as an alternative fuel with high calorific value and low carbon emissions. Additionally, hydrochar has potential as an organic fertilizer that supports sustainable agriculture. However, challenges such as the cost of oxygen production and the need for infrastructure investment remain significant hurdles.